Influence of lumbopelvic stability on deadlift performance in competetive powerlifters - Naoki Sakakibara; Sohee Shin; Tsuneo Watanabe; Toshio Matsuoka (University of Banja Luka, Faculty of physical education and sport, 2014)
The deadlift exposes the spine to extreme loads and requires adequate lumbopelvic (core) stability. Deadlift performance may be influenced by the neuromuscular control of the trunk. In this study, we aimed to compare the transversus abdominis contractile rates in an elite powerlifter with those of a control group during deadlift and estimate the relationships between core stability and deadlift performance. In the present controlled laboratory study, 16 powerlifters [8 male national-level powerlifters and 8 male regional-level powerlifters (control group)] were tested for changes in transversus abdominis thickness to evaluate transversus abdominis contractility at each deadlift phase using ultrasound imaging. Compared with the control group, the elite powerlifters showed a higher transversus abdominis contractile rate when the weight was at knee level (2.16 vs. 1.74; p = .04). There were no significant differences between the transversus abdominis contractile rates in both groups when the weight was at the floor and top level. This study reveals that deadlift performance may be influenced by transversus abdominis contractility (lumbopelvic stability).